THE CHARACTER AND SETTING IN THE NOVEL “ABOUT YOU” BY TERE LIYE - Nana Andriana; Oom Rohmah (Universitas Indraprasta PGRI, 2019)
Abstrak. This research is aimed at analyzing the Character and Setting in the Novel “About You” by Tere Liye. The method used in this research is content analysis which is to describe the Character and Setting in the novel. Data are obtained, analyzed and described based on the sentences in the novel; The Character divided into 2 types they are personal character and the attitude of personal. Setting shows the highest percentage 130 or 86%, while Character shows 22 or 14%. Character shows the highest percentage is caused by the complex sentences mostly describe someone or things in mostly sentences in the novel. Meanwhile, character in time shows 154 or 63%, setting 46 or 19%, reason 35 or 14%, condition 6 or 2%, and concession 4 2%. Antagonist and protagonist in time shows the highest percentage caused by most sentences tell about the time in almost every page. The highest percentage for the character is protagonist. Because Sri is the central for all of everything and she is a woman who has many things that should be kept. She has to keep all of assets that he has. The highest percentage in this setting is respect. Why? Because Sri and Zaman Zulkarnain are main character by every place and they are very humble for all of people around of them.Key words : Character and setting in the novel. protagonist, antagonist, flat.